How R&D Staff’s Improvisation Capability Is Formed: A Perspective of Micro-Foundations - He, Hui; Bai, Yan; Gao, Junguang; Xie, Jinqiang (Frontiers in Psychology, 2020)
The study examines how R&D staff improvisation capability is formed based on theory of micro-foundations, that is, how R&D individuals, experience and external knowledge gathering, and minimal structure interact and work on their improvisation capability together. The results show that: (1) R&D staff’s experience and external knowledge gathering have linear influences on their improvisation capability respectively; (2) minimal structure has a curvilinear impact on improvisation capability; (3) minimal structure has a curvilinear moderating effect on the relationship between experience, external knowledge gathering and improvisation capability respectively. The study suggests that managers keep minimal structure at the moderate level to promote their people’s improvisation capability.